2014
DOI: 10.1002/2014gl061471
|View full text |Cite
|
Sign up to set email alerts
|

The winter helium bulge revisited

Abstract: A newly implemented helium module in the National Center for Atmospheric Research-ThermosphereIonosphere Electrodynamics general circulation model offers the first opportunity in three decades to describe helium behavior in the context of a first principles, self-consistent model and to test early theories of wintertime helium bulge formation. This study shows general agreement with the findings of Reber and Hays (1973) but articulates the definitive role of vertical advection in the bulge formation. Our findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…X. Liu et al (2014b) provide a brief review of other early observational and theoretical studies. Fig.…”
Section: Seasonal-latitudinal Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…X. Liu et al (2014b) provide a brief review of other early observational and theoretical studies. Fig.…”
Section: Seasonal-latitudinal Variationsmentioning
confidence: 99%
“…X. Liu et al (2014b) studied the helium bulge using a newly implemented helium module in TIE-GCM. In contrast to the inter-hemispheric transport mechanism of Mayr and Volland (1972), they found that vertical advection (driven by horizontal wind divergence) and molecular diffusion are the dominant processes.…”
Section: Seasonal-latitudinal Variationsmentioning
confidence: 99%
“…Hays et al [] stated unequivocally that “it is not divergences that cause compositional changes, but the vertical motions resulting from divergence in the wind field that cause the major changes in composition.” Likewise, Burns et al [], comparing the strength of individual terms in the differential composition equation, found that the vertical advection term dominated and that the horizontal advection term was of the incorrect sign to sustain such seasonal distributions. Further tests by Liu et al [] simulated a light minor species in a general circulation model, with various transport terms “switched” on and off. Significant seasonal accumulations were only seen during simulations in which the vertical advection term was turned on, while the effects of horizontal advection on the seasonal distribution were much less significant.…”
Section: Introductionmentioning
confidence: 99%
“…We find that a seasonal interhemispheric transport of light constituents does in fact occur and is directly responsible for the observed winter‐time thermospheric enhancements. Many of the conclusions drawn by Burns et al [], Liu et al [], and Burns et al [] still hold true, with vertical advection being the most crucial term in the composition equation. However, we elucidate the principal role of an interhemispheric transport of light species in determining the strength of this vertical advection term, and thus, the global distribution of light species.…”
Section: Introductionmentioning
confidence: 99%
“…It is straightforward to show that the effect of these terms is small when the mass mixing ratio of the minor species in question is also small. Helium as a minor species in the TIE-GCM was recently implemented by Liu et al [35]. While this approach demonstrated the model's ability to accumulate helium in the winter hemisphere, it required the ad hoc inclusion of helium into the scale height calculation in order to avoid unrealistically high values during long simulations.…”
Section: Implementing Helium As a Major Speciesmentioning
confidence: 99%